Betty and Pansy's severe queer review of New York City : an irreverent, opinionated guide to the bars, clubs, restaurants, cruising areas, bookstores, and other attractions of lesbian and gay manhatten - Pearl, Betty; Bradshaw, Pansy (San Francisco : Bedpan Productions, 1994)
Fonds Suzan Daniel (FSD)
Engels
Brochure